A Clinical Study of Steroid Induced Dermatoses - Parajuli, Sudip; Paudel, Upama; Poudyal, Amod Kumar; Pokhrel, Dinesh Binod (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Introduction: Steroid induced dermatoses on face are one of the common presentations in Dermatological practice. Objectives: 1) Understand the clinical patterns of adverse effects of long term abuse of topical steroid on face and 2) Assess the factor which promotes its abuse. Materials and Methods: This was a descriptive exploratory cross-sectional study carried out from December, 2013 through November, 2014. A total of 39 patients fulfilling the inclusion criteria were enrolled into the study. All the study variables were recorded using preformed structured questionnaire and analyzed. Results: The following effects of steroid abuse on face were seen: pruritus (38.5%), burning (15.4%), eythema (74.4%), telangiectasias (66.7%), acneiform eruptions (59%), comedones (35.9%), xerosis (55.1%), photosensitivity (51.3%), rebound phenomenon (38.5%) and others (38.5%). Most of them used steroids on recommendation of their friends (38.5%) and pharmacists (20.5%). All of them used steroid for different dermatoses on their face. Limitations: This is a hospital-based small-scale study and might not be true picture of problem in the community. Conclusion: Long term use of steroid on face results in different clinical presentations. Most of the patients used steroid on recommendation of their friends facilitated by easy availability of the drug over- the -counter.